Building brand websites - Bains, Jon (Henry Stewart Talks, 2009)
Brand websites: the past and present, Points to consider before you begin, The new consumer, The importance of trust, What is brand ownership?, Who are the brand owners?, Building trusted brand communities, Facilitation, involvement, transparency and generosity, It is all about relationships and expectations, Brand and e-commerce integration, Microsites
Archived at 2022/04/11